2020
DOI: 10.3389/fpsyg.2020.581908
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leisure Satisfaction in Serious Leisure and Subjective Well-Being: Evidence From Chinese Marathon Runners

Abstract: The topics of serious leisure and subjective well-being have been discussed extensively in previous research. It is generally acknowledged that people prefer to experience deeper satisfaction and happiness through serious participation in leisure-time physical activities. However, it is essential to examine the relationship between serious leisure and subjective well-being in an urban setting as well as the mediating effect of leisure satisfaction. Data were collected from 447 recreational runners at the 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Affect had the highest mean value (M = 3.62, SD = 0.94) on the recreation specialization scale, followed by cognition (M = 3.47, SD = 0.99); behavior had the lowest mean value (M = 2.89, SD = 1.04). These findings are similar to those reported in recent research [ 12 , 16 ]. The respondents also reported feelings of high self-efficacy (M = 7.36, SD = 2.28), suggesting their strong confidence to keep running.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Affect had the highest mean value (M = 3.62, SD = 0.94) on the recreation specialization scale, followed by cognition (M = 3.47, SD = 0.99); behavior had the lowest mean value (M = 2.89, SD = 1.04). These findings are similar to those reported in recent research [ 12 , 16 ]. The respondents also reported feelings of high self-efficacy (M = 7.36, SD = 2.28), suggesting their strong confidence to keep running.…”
Section: Resultssupporting
confidence: 93%
“…Per statistical data, in 2020, over 1800 marathon events (with over 800 participants) were held in 337 cities all over China, attracting more than 7.13 million participants, a significant increase in comparison with 5.84 million runners in 2018 (Chinese Athletica Association, 2020). Recent studies confirm that being seriously involved in long-distance running has a positive impact on the marathoner’s subjective well-being [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the literature Ngai (2005) and Tian et al (2020) reached different results. Despite the high level of smartphone addiction of people with regular income, there was no statistically significant difference.…”
Section: Discussionmentioning
confidence: 93%
“…The gender's main effect on leisure satisfaction levels was not significant, and there was no significant difference in the subdimensions, which did not overlap with the findings of Ngai (2005), Serdar and Ay (2016), Serdar et al (2018), Chun et al (2012), Çelik et al (2014), andMuzindutsi andMasango (2015). However, Yaşartürk and Bilgin (2019) and Tian et al (2020) found similar results. In light of the studies in the literature, it is suggested that the differences between study findings can stem from using different sample groups.…”
Section: Discussionmentioning
confidence: 64%